Examination of attitudinal and intentional drivers of non-deceptive counterfeiting in a South Asian context - Mir, Imran Anwar (Journal of Business Economics and Management, 2013)
Counterfeiting trade is emerging as a parallel industry across the nations. Governments and legal bodies across the nations introduced counter-strategies to setback the rapid growth of this parallel industry. Yet these strategies failed to gain the desired results. Previous studies found political corruption and improper implementation of anti-counterfeiting strategies and laws main reasons for this failure. This study intends to examine the influence of word of mouth, ethical and legal sensitivities on consumers’ attitudes toward the non-deceptive counterfeit mobile handsets in a South Asian context. In addition, this study aims to assess the direct impact of affordability, legal sensitivity, and easy availability on consumers’ intentions to purchase the non-deceptive counterfeit mobile handsets. The results show that positive word of mouth about non-deceptive counterfeits and less sensitivity to ethics positively influence consumers’ attitudes toward the non-deceptive counterfeit mobile handsets. Legal sensitivity does not affect consumers’ attitudes toward the non-deceptive counterfeits. Affordability of the non-deceptive counterfeit mobile handsets has a profound impact on consumers’ purchase intentions. Findings of this study are useful for legal authorities and multinational companies in developing result oriented anti-counterfeiting strategies in South Asian markets.